Phylogenetic analyses of 18S rDNA sequences reveal a new coccoid lineage of the Prasinophyceae (Chlorophyta) - Fawley, M W; Yun, Y; Qin, M (Journal of Phycology, 2000)
Phylogenetic analyses of 18S rDNA sequences from 25 prasinophytes, including 10 coccoid isolates, reveals that coccoid organisms are-found in at least three prasinophyte lineages, The coccoid Ostreococcus tauri is included in the Mamiellales lineage and Pycnococcus provasolii is allied with the f dfellate Pseudoscourfieldia marina. A previously undescribed prasinophyte lineage is comprised of the coccoid Prasinococcus cf. Capsulatus (CCMP 1407) and other isolates tentatively identified as Prasinococcussp. (CCMP 1202, CCMP 1614, and CCMP 1194), as well as three unnamed coccoids (CCMP 1193, CCMP 1413, and CCMP 1220). No flagellate organisms are known from this lineage. Organisms of this new lineage share some characteristics of both the Pycnococcaceae and the Mamiellales, although relationships among these separate lineages were not supported by bootstrap analyses. An additional unnamed coccoid isolate (CCMP 1205) is separate from all major prasinophyte lineages. The analyses did not resolve the relationships among the major prasinophyte lineages, although they support previous conclusions that the Prasinophyceae are not monophyletic.
Keywords: ALGAL CAROTENOIDS; coccoid algae; EVOLUTIONARY TREES; Gen; GREEN-ALGAE; LIGHT-HARVESTING COMPLEX; MICROMONADOPHYCEAE CHLOROPHYTA; Prasinophyceae; PRASINOXANTHIN; PSEUDOSCOURFIELDIA-MARINA; rcc; RDNA; RIBOSOMAL-RNA SEQUENCES; Sequence Analysis; sp-nov